A model system for the analysis of gene exclusion: cystic fibrosis and chromosome 19. Issue 5 (October 1986) - Wainwright, B; Farrall, M; Watson, E; Williamson, R
Abstract : We have used multilocus analysis to exclude the cystic fibrosis locus from six polymorphic DNA markers covering most of chromosome 19. A substantial increase in the confidence for exclusion was obtained using the computer programme LINKAGE compared to analysis of pairwise lod scores. A structured approach to the analysis of linkage to autosomal recessive inherited diseases where the biochemical defect is not known is described.